Patients' experience with and perspectives on neuromodulation for pain: a systematic review of the qualitative research literature. Issue 8 (August 2020) - McCarron, Tamara L.; MacKean, Gail; Dowsett, Laura E.; Saini, Manik; Clement, Fiona
Abstract : Abstract: Chronic pain has far-reaching impacts on a person's life and on society more broadly. After failure or intolerance of conservative treatments, neuromodulation may be an option for a subgroup of patients. However, little is known about the patient experience of neuromodulation. We conducted a systematic review of published qualitative research on patient experience with neuromodulation for chronic pain. Four databases were searched: MEDLINE, EMBASE, Psych INFO, and all EMB reviews, from inception to December 4, 2019. We used narrative synthesis to identify key findings from the included studies. The data were qualitatively analyzed using a modified constant comparative analysis to identify key themes across the studies. Seven thousand five hundred forty-two unique citations were retrieved. Sixty-four abstracts were selected by the reviewers and continued to full-text review. After full-text review, 57 studies were excluded with 7 studies included in this systematic review. The included studies were of high quality. Four broad themes emerged: (1) living with chronic pain, (2) expectations, (3) managing challenges, and (4) regaining normalcy. Neuromodulation should be part of an overall pain management plan that may include the need for ongoing emotional and psychosocial support. A deeper knowledge of the patient experience with neuromodulation will assist care teams in providing meaningful support to patients. The results of this study suggest that further research is needed to support neuromodulation as an option for patients living with chronic pain. Abstract : Supplemental Digital Content is Available in the Text.